1988
DOI: 10.1111/j.1532-5415.1988.tb07176.x
|View full text |Cite
|
Sign up to set email alerts
|

Anergy Testing in Nursing Home Residents

Abstract: Delayed cutaneous hypersensitivity (DCH) testing is commonly used to determine exposure to Mycobacterium tuberculosis and in the evaluation of cellular-mediated immunity. Many reports indicate that anergy to ubiquitous antigens is common in the elderly. Recent studies suggest that anergy in the aged is not common when five or more antigens are used. Because it is often difficult to purchase singularly or apply a larger number of quality DCH antigens, we investigated the usefulness of the Multitest CMI in 29 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…1). This would indicate that the elderly nursing home population in this study is comparable to those studied by others [5,[10][11][12]15]. Moreover, despite variations in our sample study group ( fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…1). This would indicate that the elderly nursing home population in this study is comparable to those studied by others [5,[10][11][12]15]. Moreover, despite variations in our sample study group ( fig.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, several studies have shown that the decrease in DTH reaction could be less a function of age than chronic illness and frailty, especially among residents of nursing homes [18,[20][21][22]. On the other hand, even among frail nursing home patients, negative DTH reac tion (anergy) does not appear to correlate with appearance of clinical disease, i.e., the 10-50% reported frequency of DTH anergy [5,6,9,11,12,16,18,20, 23] appears to be higher than the frequency of residents who experience disorders or infections in which the attack rate or pathogenesis is dependent on the integrity of CMI. In addition, a di minished DTH reaction may not be accom panied by a comparable decline in other pa rameters of CMI, and DTH anergic elderly have been reported to mount a vigorous PPD reaction following the development of acute tuberculosis [5,24], Several investiga tions have demonstrated a correlation be tween diminished DTH reaction and in creased mortality [4,6,25], suggesting an association between immunologic vigor and survival, or possibly a causal role of dimin ished immunologic integrity on survival.…”
mentioning
confidence: 99%
“…The Multitest CMI has 8 test heads preloaded with the following test substances: tetanus toxoid, diphtheria toxoid, streptococcus antigen, old tuberculin antigen, glycerin negative control, candida antigen, trichophyton antigen, and Proteus antigen. The Multitest CMI provides a standardized, reproducible means to test cell-mediated immunity (17,18). For the PPD test, 0.1 mL of the PPD antigen (5-unit strength) was applied intradermally.…”
Section: Skin Testingmentioning
confidence: 99%